Sliding Mode Control Of A Hydraulically Actuated Active Suspension - Md. Sam, Yahaya; Osman, Johari Halim Shah (Penerbit UTM Press, 2006)
The objective of this paper is to present a new mathematical model and robust control technique for modeling and control of an active suspension system with hydraulic dynamics for a quarter car model. The purpose of a car suspension system is to improve the riding quality while maintaining good handling characteristics subject to different road profiles. The objective of designing a controller for a car suspension system is to improve the riding quality without compromising the handling characteristic by directly controlling the suspension forces to suit the road and driving conditions. In this paper, a new mathematical model is presented which will give a much more complete mathematical representation of a hydraulically actuated suspension system for the quarter car model. However, the mathematical model obtained suffers from mismatched condition. In order to achieve the desired ride comfort and road handling and to solve the mismatched condition, a proportional integral sliding mode control technique is presented to deal with the system and uncertainties. The effect of boundary layer thickness selection in the proposed controller is also presented. Extensive simulations are performed and the results showed that the proposed controller performed well in improving the ride comfort and road handling for the quarter car model using the hydraulically actuated suspension system.